The need of dermatologists, psychiatrists and psychologists joint care in psychodermatology - Roberto Doglia Azambuja (Sociedade Brasileira de Dermatologia, 2017)
Abstract: The mind-skin connection has been studied since the nineteenth century. The last 40 years have set the development of new research areas which allowed the clarifying of how these two dimensions interact. The diseases that involve skin and mind constitute the field of psychodermatology and require that specialists in dermatology, psychiatry and psychology together and integrated take part in it, since skin, nervous system and mind are simultaneously affected. This paper aims to expose how psychodermatoses are currently conceptualized and the need of integration of these three specialties for conveniently treating the patients.